If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-7x/3)-1=-1-(7x/8)
We simplify the equation to the form, which is simple to understand
(-7x/3)-1=-1-(7x/8)
Remove unnecessary parentheses
-2.3333333333333x-1=-1-( + 0.875x)
Remove unnecessary parentheses
-2.3333333333333x-1=-1-0.875x
We move all terms containing x to the left and all other terms to the right.
-2.3333333333333x + 0.875x=-1+1
We simplify left and right side of the equation.
-1.4583333333333x=0
We divide both sides of the equation by -1.4583333333333 to get x.
x=-0
| 35=x+(2x-1)+(2+14x) | | 4x-10+7(x-3)=0 | | 6(2+7x)+3x=9+6(9+8x) | | (2x+4y)+(2x-y)-(x-2y)= | | 16-(3x-15)=4x-(9x-9) | | 3=8x-7x+4 | | y^3(3-4x^2)=7x-y^4 | | 2(x+3/4)=9(1/6-x) | | -8x+9x+6=9 | | 6x-8x+2=-13 | | 35=x+(2x-1)+(3(2x-1)+3) | | 35=x+(2x-1)+(3(2x-1)+2) | | 35=x+(3x-1)+(4(3x-1)+2) | | x(x+5)+1=(x+6)(x+6) | | 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 |